Real-time MRI for precise and predictable intra-arterial stem cell delivery to the central nervous system. Issue 7 (July 2017) - Walczak, Piotr; Wojtkiewicz, Joanna; Nowakowski, Adam; Habich, Aleksandra; Holak, Piotr; Xu, Jiadi; Adamiak, Zbigniew; Chehade, Moussa; Pearl, Monica S; Gailloud, Philippe; Lukomska, Barbara; Maksymowicz, Wojciech; et al.
Stem cell therapy for neurological disorders reached a pivotal point when the efficacy of several cell types was demonstrated in small animal models. Translation of stem cell therapy is contingent upon overcoming the challenge of effective cell delivery to the human brain, which has a volume ∼1000 times larger than that of the mouse. Intra-arterial injection can achieve a broad, global, but also on-demand spatially targeted biodistribution; however, its utility has been limited by unpredictable cell destination and homing as dictated by the vascular territory, as well as by safety concerns. We show here that high-speed MRI can be used to visualize the intravascular distribution of a superparamagnetic iron oxide contrast agent and can thus be used to accurately predict the distribution of intra-arterial administered stem cells. Moreover, high-speed MRI enables the real-time visualization of cell homing, providing the opportunity for immediate intervention in the case of undesired biodistribution.